Peran Manajemen Laba dalam Memoderasi Pengaruh Kualitas Audit terhadap Kinerja Perusahaan pada Sektor Consumer Cyclical - Aqilah Haya Amani; Sudrajat Sudrajat; Ratna Septiyanti (AKUNTANSI 45, 2026)
This study aims to examine the relationship between audit quality and firm performance with earnings management acting as a moderating variable in consumer services sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research applied a quantitative approach using secondary data derived from annual financial statements and independent auditor reports. The sample was selected through purposive sampling, resulting in 34 companies with a total of 170 observations. Data analysis was conducted using panel data regression with the Moderated Regression Analysis (MRA) approach. Firm performance was proxied by Return on Assets (ROA), while audit quality was measured using audit tenure. Earnings management was measured through discretionary accruals based on the Modified Jones Model. The findings reveal that audit quality does not have a significant effect on firm performance. However, earnings management was found to weaken the relationship between audit quality and firm performance. These results indicate that higher levels of earnings management practices may reduce the effectiveness of audit quality in reflecting the company’s actual performance reliably.